Revenge Porn Sebagai Bentuk Kekerasan Seksual Ditinjau Berdasarkan Teori Hukum Pidana - Ratu Wida Widyaningsih Suhandi; Muhammad Fahrudin; Taufiqurrohman Syahuri (Hakim, 2024)
Revenge porn as a form of sexual violence is an interesting thing to observe and study, Indonesia has passed Law Number 12 of 2022 on Sexual Violence, it turns out that the passing of the TPKS Law has not become a fundamental reference for perpetrators of sexual violence until now sexual violence in Indonesia still occurs frequently. Normative legal research or library legal research (libary research), with a legislative approach (statue approach), conceptual approach (conceptual approach), comparative approach (comparative approach), historical approach (historical approach). The nature of the research used in this research is descriptive-prescriptive, the author uses content analysis. The results of the research Revenge porn as a form of sexual violence can be reviewed based on criminal law theory which consists of punishment, guilt and criminal liability.